Goals of COPD treatment: Focus on symptoms and exacerbations. (May 2020) - Vogelmeier, Claus F.; Román-Rodríguez, Miguel; Singh, Dave; Han, MeiLan K.; Rodríguez-Roisin, Roberto; Ferguson, Gary T.
Abstract: Chronic obstructive pulmonary disease (COPD) is currently a leading cause of death worldwide, and its burden is expected to rise in the coming years. Common COPD symptoms include dyspnea, cough and/or sputum production. Some patients may experience acute worsening of symptoms (known as an exacerbation), and therefore require additional therapy. Exacerbations are mainly triggered by respiratory infections and environmental factors. Healthcare professionals face many challenges in COPD management, including the heterogeneity of the disease and under-reporting of symptoms. The authors review these challenges and provide recommendations for the best methods to assess COPD. The goals of COPD treatment include recognising the impact that both symptoms and exacerbations have on patients' lives when considering optimal patient-focused management. The review discusses the need for COPD management strategies to include both pharmacologic and non-pharmacologic approaches and provides recommendations for monitoring treatment outcomes and adjusting management strategies accordingly. Novel treatment strategies including precision medicine and point-of-care testing are also discussed. Graphical abstract: Image 1 Highlights: Challenges of COPD management include disease heterogeneity and under-diagnosis. The best available tools should be used for COPD diagnosis and assessment. Optimal management of COPD includes recognizing both symptoms and exacerbations. Both pharmacologic and non-pharmacologic treatment strategies should be considered. Novel strategies (e.g. precision medicine, point-of-care testing) may be of value.